Moose magic for kids - Fair, Jeff.; Francis, Michael H. (Michael Harlowe), 1953-; Stevens, Sandy; Fair, Jeff. (Milwaukee, Wis. : Gareth Stevens Pub., 1995)
Describes the habitat, physical characteristics, and behavior of the moose of the wild north country.
Based on: Moose for kids. 1992.
Includes index.
Keywords: Moose -- Juvenile literature; Moose